Evaluation Of Haemoglobin Level and Platelet Count In Neonates With And Without Retinopathy Of Prematurity - Di, Lim Zi (2021)
Aim: Haemoglobin and platelet have been postulated to play a role in the development of retinopathy of prematurity (ROP). This study aimed to compare weekly mean haemoglobin level and platelet count between ROP and non-ROP infants in the first six weeks of life. Method: Ninety-three premature infants with birth weight less than 1.5 kg and gestational age less than 32 weeks were recruited in Hospital Universiti Sains Malaysia from 2017 to 2019. Each ROP case was individually matched (1: 2) to two non-ROP cases. Weekly mean haemoglobin level, weekly mean platelet count, and other related risk factors were documented. Result: Thirty-one infants with ROP and 62 infants with non-ROP were recruited. Of those with ROP, 8 had stage 1 ROP, 6 had stage 2 ROP, 16 had stage 3 ROP. The mean birth weight and gestational age of the ROP group was 962.2 g and 27.6 weeks while the non-ROP group was 1056.9 g and 28.5 weeks respectively. We found significant differences in the weekly mean platelet counts between ROP and non-ROP infants from week two to week six of life (p=0.003). A significant difference was also found when comparing weekly mean haemoglobin level at week one of life (p=0.003). However, no significant difference was found in the weekly mean platelet count (p=0.489) and weekly mean haemoglobin level (p=0.292) after adjusting to covariates. Conclusion: There is no significant difference in mean haemoglobin level and platelet count in the first six weeks of life between ROP and non-ROP infants after adjusting to confounding factors like sepsis, bronchopulmonary dysplasia and blood transfusion.